Development of Community-Based Growth and Development Physiotherapy Services in Karangmalang District - Angga Pebrian Saputra; Farid Rahman (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Based on the Basic Health Research (RISKESDAS) report in 2018, 39, 32% of Karangmalang District, Sragen City had problems with child growth and development. The main factor of this problem is because parents hide their children at home who are experiencing child development problems due to embarrassment to the surrounding community and the supporting factors of this problem are due to the lack of parents' economy for treatment at the hospital, and lack of education in understanding the importance of health in children's growth and development. The purpose of this activity is to provide education and understanding to parents in Karangmalang District about the importance of healthy growth and development in children. The conclusion of the activity can contribute to the community of Karangmalang District as an effort to provide physiotherapy services and educational efforts to parents who have growth and development problems in their children and understand better about the importance of handling physiotherapy on growth and development problems in children.